2005
DOI: 10.1007/bf02711166
|View full text |Cite
|
Sign up to set email alerts
|

A strategic approach for preparation of oxide nanomaterials

Abstract: Abstract. A microwave assisted solvothermal method is described for rapid preparation of nano-oxides. This method is based on exploiting differential dielectric constants to induce preferred heating and decomposition of the oxide precursors in the presence of suitable capping agents. This strategic approach has been used to prepare nanopowders of MgO,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…Sol-gel methods and some solvothermal methods produce poorly crystalline particles and require an additional crystallization step at high temperatures, giving rise to highly agglomerated ZrO2 NCs. 5,[14][15][16][17][18][19] Other methods suffer from the formation of mixed ZrO2 phases 5,20 and in general high temperatures and/or long reaction times 2,4,9,21 are required. These drawbacks depend on a combination of different factors: the selected synthesis method, presence or absence of pressure, difference in precursor solution or pH… One of the most appealing synthesis routes was introduced by Niederberger et al and uses a solvothermal autoclave method in benzyl alcohol to create a variety of crystalline metal oxide NCs (ZrO2, HfO2, In2O3, Ga2O3 …) at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Sol-gel methods and some solvothermal methods produce poorly crystalline particles and require an additional crystallization step at high temperatures, giving rise to highly agglomerated ZrO2 NCs. 5,[14][15][16][17][18][19] Other methods suffer from the formation of mixed ZrO2 phases 5,20 and in general high temperatures and/or long reaction times 2,4,9,21 are required. These drawbacks depend on a combination of different factors: the selected synthesis method, presence or absence of pressure, difference in precursor solution or pH… One of the most appealing synthesis routes was introduced by Niederberger et al and uses a solvothermal autoclave method in benzyl alcohol to create a variety of crystalline metal oxide NCs (ZrO2, HfO2, In2O3, Ga2O3 …) at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there are large number of reports for the synthesis of nanostructured ZnO such as precipitation/mechanical milling [21], microemulsion [22], ultrasonic radiation [23], microwave irradiation [24], solution combustion, microwave assisted solvothermal [25] and sol-gel method [26]. However, in recent years, the electrochemical method of synthesis of nanosized metal oxide powder and films have acquired a considerable interest because of its simplicity, low operating temperature and viability in commercial production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be assumed that diethyl ether molecules are not decomposed under microwave irradiation. Additionally, during the microwave synthesis of oxides, K. J. Rao et al [12] reported the formation of diethyl ether molecules by condensation of alcohol molecules. Moreover, MS-coupled DTA/TG-investigations on the dry aluminium alkoxy fluoride clearly showed the formation of diethyl ether and water as result of Lewis acid (Al 3 + ) induced alcohol condensation.…”
mentioning
confidence: 98%